Patient versus provider incentives in long-term care - Martin B. Hackmann; R. Vincent Pohl; Nicolas R. Ziebarth (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
How do patient and provider incentives affect the provision of long-term care? Our analysis of 551 thousand nursing home stays yields three main insights. First, Medicaid-covered residents prolong their stays instead of transitioning to community-based care due to limited cost-sharing. Second, when facility capacity binds, nursing homes shorten Medicaid stays to admit more profitable out-of-pocket private payers. Third, providers react more elastically to financial incentives than patients. Thus, targeting provider incentives through alternative payment models, such as episode-based reimbursement, is more effective than increasing patient cost-sharing in facilitating transitions to community-based care and generating long-term care savings.
Keywords: H51; H75; I11; I13; I18; J14; 330; Long-Term Care; Nursing Homes; Patient Incentives; Provider Incentives; Cost-Sharing; Episode-Based Reimbursement; Medicaid